Evaluation of Sexist and Prejudiced Attitudes Toward Homosexuality in Spanish Future Teachers: Analysis of Related Variables - Heras-Sevilla, Davinia; Ortega-Sánchez, Delfín (Frontiers in Psychology, 2020)
Discrimination and inequality on the basis of gender and sexual diversity remain prevalent in today's society (Barrientos & Cárdenas, 2013; Beck et al., 2010; Dispenza et al., 2012; Dugan et al., 2012). These situations of exclusion and rejection show the need to train individuals and organizations in the prevention of violence, harassment and inequality (Kattari, et al., 2018). Teacher training, both initial and ongoing, is a fundamental axis of action, and consequently, the study of the opinions and beliefs of students and teachers on these issues. This research, therefore, analyses the sexist and prejudiced attitudes towards homosexuality of future teachers in the Spanish educational system. The sample of this research is made up of 452 students in the Degree in Primary Education Teaching and in the Master's Degree in Compulsory Secondary Education, Upper Secondary Education, Vocational Training and Language Teaching (MUPES) with an average age of 24.74 (SD= 6.51). For the collection of information, a questionnaire was used consisting of questions on sociodemographic and cultural aspects, the Inventory of Ambivalent Sexism (ASI) by Glick and Fiske (1996) validated in Spanish by Expósito et al. (1998), and the Scale of Attitudes of Heterosexuals towards Homosexuals (HATH) by Larsen et al. (1980), validated in Spanish by Barrientos and Cárdenas (2010). The main results include the presence of significant differences (p < .01) in the levels of ambivalent sexism (hostile and benevolent) and in the maintenance of negative attitudes towards homosexuality according to sex and political ideology.